Inhibition of XPO1 by selinexor enhances terminal erythroid maturation through modulation of HSP70 trafficking in severe β0-thalassemia/HbE - Pinyaphat Khamphikham; Adisak Tantiworawit; Songyot Anuchapreeda (PLoS ONE, 2025)
Ineffective erythropoiesis is a hallmark of β-thalassemia, characterized by impaired erythroid maturation and increased apoptosis of erythroid precursors in the bone marrow, resulting in chronic anemia. Heat shock protein 70 (HSP70) trafficking has emerged as a critical regulator of erythroid maturation. Inhibition of nuclear export protein exportin-1 (XPO1) retains HSP70 in the nucleus, thereby promoting terminal erythroid maturation (TEM) through stabilization of the transcription factor GATA1. In this study, we screened nine XPO1 inhibitors, including the natural compounds curcumin, piperlongumine, plumbagin, and oridonin, as well as the synthetic agents KPT-185, KPT-276, selinexor, verdinexor, and eltanexor, in erythroid progenitors from patients with severe β0-thalassemia/HbE to identify the most effective inducer of TEM and to investigate the downstream molecular mechanisms involved. Selinexor, an FDA-approved drug for multiple myeloma, showed the greatest efficacy in enhancing TEM across nine independent patient samples without altering hemoglobin composition. Combination treatments with hydroxyurea (a γ-globin inducer) and SIS3 (a SMAD3 inhibitor) confirmed selinexor’s dominant effect. Mechanistically, selinexor-induced TEM was associated not only with stabilization of nuclear HSP70 and GATA1 but also with a dose-dependent increase in cytoplasmic HSP70. These findings suggest that cytoplasmic HSP70 trafficking may contribute to erythroid maturation in severe β0-thalassemia/HbE, implicating regulatory pathways beyond nuclear GATA1 stabilization. Collectively, our findings highlight the therapeutic potential of repurposing selinexor to enhance erythroid maturation in β-thalassemia and suggest that cytoplasmic HSP70 trafficking warrants further investigation as a contributor to terminal erythroid maturation in β-thalassemia.